Ushfuriyah / Syekh Muhammad bin Abu Alwy Amru Ghazali ; editor Abud Azid Muttaqin. - MUHAMMAD BIN ABU BAKAR AL USHFURI, Syekh; Muhammad Alwwy Amru Ghazali; Abud Azid Muttaqin (Diva Press, 2016)
268 hlm. ; 20 cm.